The Coordination Between Youth Institutions and Its Implications on the Strategy for Youth Delinquency Prevention - Sacia Ghenam; Khadidja Lebbihi (Guidena)
Youth have received the highest level of attention aimed at their care under strategies adopted by the youth and sports sector, as it is among the sensitive sectors in the youth system and constitutes one of the future strategies in the state's policy in terms of controlling the services that should be provided and renewed for youth. This involves envisioning their needs based on age, gender, educational level, geographical region, and urban and social environment to prevent them from deviating from the right path.